(untitled) (International Journal of Engineering and Computer Science, 2017)
Software quality is very crucial in the development of software systems.Software Metrics help in identifying potential problem areas and finding the problems in those areas decreases the cost. C&K metric suite is one of the well known and most popular metric suites known for measuring the design of object oriented programs. As we know that testing determines the conformance of the software’s implementation to its specification so it is one of the important phases in object-oriented systems. This paper focuses on the analysis of the impact of various C&K metrics on testing.